Interim Report on Minor Irrigation Works in Mysore State - Committee on Plan Projects Planning Commission (Planning Commission, Government of India, 1968)
The Interim Report on Minor Irrigation Works in Mysore State (April 1959) examines the deteriorating condition of traditional tank irrigation systems and proposes strategic measures to restore their agricultural productivity. Central to the Report is the recommendation of a desilting-cum-reclamation scheme, initiated experimentally at the Hebbal Tank, aimed at recovering silted tank beds for cultivation and financing reclamation through the sale of reclaimed land. The Report highlights widespread tank silting, soil erosion in catchment areas, and high evaporation losses as major constraints on irrigation efficiency. It emphasizes improved water resource management, integration of irrigation and agricultural administration, and the adoption of less water-intensive cropping patterns. By combining technical interventions with administrative reform and community participation, the Report outlines a pragmatic framework for revitalizing minor irrigation and strengthening agricultural sustainability in Mysore State and neighboring regions.
Committee on Plan Projects (Irrigation and Power Team) New Delhi, April 1959
Keywords: Minor Irrigation Works; Mysore State Tanks; Desilting-Cum-Reclamation Scheme; Hebbal Tank Experiment; Tank Siltation Crisis; Soil Erosion Control; Catchment Area Management; Evaporation Loss Reduction; Surface and Sub-Soil Water Use; Unified Irrigation Administration; Crop Pattern Rationalization; Agricultural Land Reclamation